Sovereignty Showdown: The EU`s Constitutional Tug-of-War - MARTINS, Nuno Filipe Medeiros; NORONHA RODRIGUES, José (Revista Jurídica Portucalense, 2024)
The primacy of the European Law is, nowadays, an effective reality in the legal-constitutional system of Portugal and the Member States of the European Union. Although this assessment is frequent, the fact is that, over the years, the overwhelming structure of the EU's legislative system has come to weigh on the Constitutions of the Member States, sometimes putting the fundamental texts into question and, consequently, affecting state sovereignty. As mentioned above, even if the primacy of European Law (established in the community´s jurisprudence) is accepted, it is understood that this conception cannot be linear and the democratic legitimacy for this externally imposed constitutional transformation must be called into question, affecting the basis of the social contractualization that shaped the Constitution. It is therefore important to abandon the self-imposed “federalization” of European Law, to consolidate the healthy and desired constitutional coexistence with the norms emanating from the European legal order.